Nichols Algebras of Unidentified Diagonal Type - Angiono, Iván Ezequiel (2012)
The Nichols algebras of diagonal type with finite root system are either of standard, super or (yet) unidentified type. A concrete description of the defining relations of all those Nichols algebras was given in citeA-exp presentation. In the present paper we use this result to give an explicit presentation of all Nichols algebras of unidentified type.